2020
DOI: 10.1080/14634988.2020.1800341
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation patterns of Total Suspended Solids around the coastal areas of Bahrain, a water quality guideline

Abstract: The study provides an assessment of sand dredging activities from the bottom of the sea during 2016 in the Kingdom of Bahrain. Total Suspended Solids were analyzed from 2010 until 2016 in the northern and eastern locations according to the Manual of oceanographic observations and pollutant analyses methods. Fifty five percent of sand dredging companies complied with some legislation such as air quality and occupational health. Almost all lacked any compliancy evidence supporting environmental protection. Only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Despite being confined to the immediate footprint of projects, the dredging and disposal of sediment can increase suspended solids in the surrounded areas. For instance, Zainal et al [53] investigated the spatial and temporal variation patterns of the total suspended solids around the coastal areas of Bahrain due to dredging activities in the period 2010-2016. The study found that around 27% of the dredging companies carried out dewatering without allowing sufficient time for settling during the sand disposal process [53].…”
Section: Environmental Variablesmentioning
confidence: 99%
“…Despite being confined to the immediate footprint of projects, the dredging and disposal of sediment can increase suspended solids in the surrounded areas. For instance, Zainal et al [53] investigated the spatial and temporal variation patterns of the total suspended solids around the coastal areas of Bahrain due to dredging activities in the period 2010-2016. The study found that around 27% of the dredging companies carried out dewatering without allowing sufficient time for settling during the sand disposal process [53].…”
Section: Environmental Variablesmentioning
confidence: 99%